Electronic Commerce 2008
DOI: 10.4018/978-1-59904-943-4.ch145
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Customer Perceptions of Mobile Advertising

Abstract: A two-stage approach is employed in order to examine the influencing factors of consumer behaviors in the context of mobile advertising. The first stage of the study evaluates the correlation relationship of consumer motives for receiving mobile advertising and their attitudes toward mobile advertising. It also investigates the relationship between consumer intentions for receiving advertisements on their cellular phones and their subsequent actions once the mobile advertising was received. A negative sentimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…All constructs and their related items were extracted and supported from the previous literature. The perceived connectivity scale (Lee, 2005) was constructed based on Lee’s research, including five items. Based on the research of Wu et al , the perceived personalization scale (Wu, 2006) is constructed, including five items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All constructs and their related items were extracted and supported from the previous literature. The perceived connectivity scale (Lee, 2005) was constructed based on Lee’s research, including five items. Based on the research of Wu et al , the perceived personalization scale (Wu, 2006) is constructed, including five items.…”
Section: Methodsmentioning
confidence: 99%
“…Dholakia et al (2000) determined that user control, response, real-time interaction, connectivity, personalization/customization and interest are the components of interaction from the perspective of website visitors. In the mobile commerce environment, interactivity is perceived, which is composed of user control, responsiveness, connectivity, personalization, ubiquitous connection and context provision (Lee, 2005). In short, measuring HCI from the perspective of user perception is more intuitive and can better predict user attitude and behavior.…”
Section: Theoretical Review and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers agree that interactivity is a multidimensional concept that encompasses control, responsiveness, connectedness, and other factors (Lee, 2005;Liu, 2003;Park & Yoo, 2020). Nandi et al (2021) revealed that the perceived interactivity of a mobile app increased mobile app stickiness through utilitarian value and flow.…”
Section: Interactivity As a Unique Attribute Of Mobile Communicationmentioning
confidence: 99%
“…The former emphasizes counting the number of interactive features on a mobile app, the latter individuals' evaluations of interactivity. Researchers agree that interactivity is a multidimensional concept that encompasses control, responsiveness, connectedness, and other factors (Lee, 2005; Liu, 2003; Park & Yoo, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%